PENITIPAN GANTI RUGI DALAM PENGADAAN TANAH JALAN TOL SERPONG-BALARAJA (STUDI PUTUSAN NOMOR 422/PDT.BTH/2021/PN TNG) : Custody of Compensation in Land Procurement for the Serpong-Balaraja Toll Road (Study of Verdict Number 422/PDT.BTH/2020/PN Tng) - Fadilla Ramdani; Irene Eka Sihombing (Faculty of Law, Universitas Trisakti, 2024)
The construction of the Serpong-Balaraja toll road faced issues with the amount of compensation not matching the determined results, leading to Custody of Compensation in the District Court. This article addresses two main problems: (1) Whether the Custody of Indemnity Procedure by the Ministry of Public Works and Public Housing (PUPR) and the Director aligns with the law, and (2) How the judge ruled in the Maryati case regarding the Custody of Indemnity by the Ministry of PUPR. This descriptive normative research uses literature studies for data collection, analyzed qualitatively, with conclusions drawn using the deductive method. It was found that the Ministry of PUPR and the Director General of Bina followed the consignment process correctly according to the laws, yet under Presidential Regulation Number 71 of 2012, if the eligible party rejects the compensation amount set by a final court decision, the consignment process fails to reach an agreement. Thus, the conclusion is that the Indemnity Deposit Procedure by the Ministry of PUPR in acquiring land for the Serpong-Balaraja toll road project did not comply with the applicable laws and regulations.